WORK-LIFE BALANCE: A STUDY OF PERSONALITY FACTORS AS A PREDICTOR OF WORK-LIFE BOUNDARY PERMEABILITY AND USE OF ENTERPRISE SOCIAL MEDIA AND TECHNOLOGY - Wu, Allison H (East Carolina University, 2017)
The purpose of this study was to investigate the relationship between personality, work-home boundary permeability, and the percentage of electronic life intrusions answered (ELT Percent). Results indicated that openness to experience, extraversion, agreeableness, and neuroticism were positively correlated with boundary permeability; however, only extraversion was significant. Agreeableness was also found to be positively correlated with ELT Percent; this relationship was found to be significant. Finally, boundary permeability was found to have a significant positive relationship with ELT Percent. Hierarchical (sequential) linear regression was used to create a model with demographic variables (age, sex, industry, and job tenure), personality factors, and boundary permeability accounting for 19.5% of the variance in the ELT Percent. The theoretical implications of the results, as well as limitations and future directions, are discussed.
Keywords: technology; work-home boundary; boundary permeability; Work-life balance; Social media; Work--Psychological aspects; Big Five model